2014
DOI: 10.3109/13816810.2014.991931
|View full text |Cite
|
Sign up to set email alerts
|

RPE65 Mutations in Two Japanese Families with Leber Congenital Amaurosis

Abstract: By using whole-exome sequencing analysis, three RPE65 mutations were identified in two Japanese patients with LCA. This approach would be useful for identification of disease-causing mutations of LCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…(32,33). This cohort within the National Health system of Costa Rica suggests a higher prevalence of RPE65 mutations than has been estimated in other populations around the world (31,34,35,36,37,38,39,40), though some studies have suggested population specific increases in RPE65 mutation prevalence (31,41). This study identified four recurrent RPE65 mutations, at least one of which was seen in 29 out of 30 cases (97%), and 20 out of 21 families (95%).…”
Section: Discussionmentioning
confidence: 66%
“…(32,33). This cohort within the National Health system of Costa Rica suggests a higher prevalence of RPE65 mutations than has been estimated in other populations around the world (31,34,35,36,37,38,39,40), though some studies have suggested population specific increases in RPE65 mutation prevalence (31,41). This study identified four recurrent RPE65 mutations, at least one of which was seen in 29 out of 30 cases (97%), and 20 out of 21 families (95%).…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, biallelic RPE65 mutations contributed to approximately 3.0% (8/269) of LCA and 0.8% (18/2133) of HRD cases. Clinically, diseases in 13 of the 18 families could be classified as LCA or EORD, which are common phenotypes previously reported to be associated with RPE65 mutations (Gu et al 1997;Marlhens et al 1997;Morimura et al 1998;Thompson et al 2000;Simovich et al 2001;Yzer et al 2003;Booij et al 2005;El Matri et al 2006;Simonelli et al 2007;Li et al 2009;Xu et al 2012;Kabir et al 2013;Verma et al 2013;Astuti et al 2016;Katagiri et al 2016). In the remaining five families with biallelic RPE65 mutations, we unexpectedly found that the phenotypes were FA-like changes in four families and high hyperopia in one family.…”
Section: Discussionmentioning
confidence: 91%
“…; Katagiri et al. ). In the remaining five families with biallelic RPE65 mutations, we unexpectedly found that the phenotypes were FA‐like changes in four families and high hyperopia in one family.…”
Section: Discussionmentioning
confidence: 97%
“…Full-field electroretinography using a light-emitting diode with a built-in electrode (LE-4000, Tomey, Nagoya, Japan) was recorded in accordance with the protocols of the International Society for Clinical Electrophysiology of Vision 34 . The procedure and conditions used in this study have been previously reported 35 , 36 .…”
Section: Methodsmentioning
confidence: 99%